EFFECTIVENESS AND ACCEPTABILITY OF READY-TO-USE THERAPUETIC FOODS AMONG MALNOURISHED CHILDREN IN A TERTIARY CARE HOSPITAL - Bashir, Abida; Zaman, Shakila (Journal of Ayub Medical College Abbottabad, 2016)
Background: Ready-to-use-therapeutic foods (RUTF) are an important component of the effective outpatient treatment of severe wasting because most of the child deaths in the world especially in developing countries is due to malnutrition. The objective of the study was to evaluate the effectiveness and acceptability of ready to use therapeutic food among malnourished children in a tertiary care hospital. Methods: An observational exploratory study based on sixty subjects with 3-120 months of age, malnourished children were chosen by universal sampling from Children Hospital Lahore, Pakistan, during the time period 1st September 2012 to 30th November 2012 with the approval of ethical committee. The study tool for investigation was a well-structured questionnaire. Results: The highest proportion of malnourished children belonged to urban areas (71.67%) and age group <24 months (65%).The effect of RUTF on weight for height and weight for age Z score from baseline to the end of follow-up was statistically significant (Paired sample t-test) (p=0.000, 0.000) but there was no significant effect of RUTF on height for age (p-value=0.14).The acceptance of food among patients was good, the proportion of patient was higher who consumed ready to use therapeutic food easily (70%), percentage of vomiting (16.7%) and complaints of diarrhoea (46.7%) after taking RUTF was less in patients. All mothers were satisfied from ready to use therapeutic foods (100%). Conclusion: Malnourished children gained weight after the short term supplementation of ready to use therapeutic food but had no significant effect on height of the patients. Its acceptability in term of taste, amount consumes and demand was good. Mother's perception was also satisfactory regarding these foods. Keywords: Malnutrition, children, ready to use therapeutic food, RUTF